(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Genetic diversity evaluation in a breeding program is essential produce robust, resilient crop varieties with improved agronomic characteristics under environmental challenges in the sustainable agro-ecosystems. Knowledge and full potential on the impact of genotypes and growing conditions on flax yield traits still incomplete. The aim of this study was to evaluated the influence of hydrothermal conditions on the development of agronomic important traits of flax, analysed agronomic characteristics and identified perspective genotypes for pre-breeding. Field investigations were carried out from 2014 to 2017 for agronomically important traits of flax. In the study was evaluated flax population with Latvian origin in 24 fibre flax genotypes and ‘Vega 2’ (ST) as the standard variety of Lithuanian origin under Latvian meteorological conditions. Correlation between flax genotypes of the agronomically important yield traits and years of the hydrothermal coefficients during the growth period were analysed. According to the results obtained that most of genotypes the significant higher plants stem yield, total plant height, technical plant height, number of seed vessels per plant were measured in the growing seasons with high humidity. However, the higher seed yield and 1000 seed weight were measured in the driest year. The correlation between flax fibre content, seed number per seed-vessel, oil content and humidity level differed in dependence on genotype. The coefficient of variability between years was higher for of stem yield when compared with seed yield. The flax genotypes ‘S13/5-7/5-93’ exhibited more stable, highest stem yield (840.0 g m-2) and high seed yield (162.2 g m-2). The flax was identified 80% samples the short and 20% the medium vegetation period.